A green separation mode of synephrine from Citrus aurantium L. (Rutaceae) by nanofiltration technology. Issue 12 (13th November 2019) - Li, Cunyu; Ma, Yun; Gu, Jiamei; Zhi, Xinglei; Li, Hemin; Peng, Guoping
Abstract: Thermal breakage of alkaloid ingredients was a common problem to which attention should be paid in the application of fruit ingredients separation. In this study, the mathematical models were established to predict the rejection of synephrine from Citrus aurantium L. (Rutaceae). The experiment showed that there was a linear relationship between operation pressure and membrane flux. Meanwhile, under the influence of solution–diffusion effect and the charge effect, the mass transfer coefficient was power functioned with initial concentration. The mathematical model showed that the predicted rejections of synephrine from Citrus aurantium extract were well approximate to real ones, and the lipid‐lowering active ingredient had effectively enriched. The predicted model of nanofiltration separation has a preferable applicability to synephrine and provides references for nanofiltration separation, especially for raw food materials with synephrine. Abstract : Thermal breakage of alkaloids ingredients was a common problem to which attention should be paid in the application of fruit ingredient separation. In this study, the mathematical models were based on the operating pressure and initial concentration to predict the rejection of synephrine. Moreover, the concentration of synephrine was effectively increased and the lipid‐lowering activity was also enhanced by using NF technology. The predicted model of nanofiltration separation has a preferable applicability to synephrine and provides references for nanofiltration separation, especially for raw food materials with synephrine.